2009
DOI: 10.3748/wjg.15.2679
|View full text |Cite
|
Sign up to set email alerts
|

Amelanotic malignant melanoma of the esophagus: Report of two cases with immunohistochemical and molecular genetic study of KIT and PDGFRA

Abstract: The author reports herein two cases of amelanotic malignant melanoma of the esophagus. Case 1 is an 87-year-old woman who was admitted to our hospital because of nausea and vomiting. Endoscopic examination revealed an ulcerated tumor of the distal esophagus, and a biopsy was taken. The biopsy showed malignant polygonal and spindle cells. No melanin pigment was recognized. Immunohistochemically, the tumor cells were positive for melanosome (HMB45), S100 protein, KIT and Platelet derived growth factor receptor-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…The presence of c-Kit mutations may contribute to response to specific tyrosin kinase inhibitor therapy, and therefore molecular screening for c-Kit mutations may be helpful for identifying alternative therapeutic options in esophageal melanoma. The occurrence of c-Kit mutations in esophageal melanoma has been reported recently in the literature, 11,12 but the studies analyzed only exons 11, 13 and 17, but not exon 9, where we could detect two mutations and which encodes for the extracellular domain of the c-Kit protein.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The presence of c-Kit mutations may contribute to response to specific tyrosin kinase inhibitor therapy, and therefore molecular screening for c-Kit mutations may be helpful for identifying alternative therapeutic options in esophageal melanoma. The occurrence of c-Kit mutations in esophageal melanoma has been reported recently in the literature, 11,12 but the studies analyzed only exons 11, 13 and 17, but not exon 9, where we could detect two mutations and which encodes for the extracellular domain of the c-Kit protein.…”
Section: Discussionmentioning
confidence: 65%
“…6,7 In both cutaneous and noncutaneous melanomas, various genetic aberrations occur and among them c-Kit, RAS-isoform and BRAF alterations are found at various frequencies. [8][9][10] However, molecular information about primary esophageal melanoma is scarce because of its rarity, and recent reports represent only small series or case reports with analysis of single or few molecular aberrations: most recently, Terada et al 11 have reported two cases from Japan where a PDGFR-A and a c-KIT mutation analysis was performed, without demonstrating a PDGFR-A and a c-KIT mutation in these tumors. Sekine et al 12 have described a larger series of 16 esophageal melanomas from Japan as well.…”
mentioning
confidence: 99%
“…To diagnose melanoma of the oesophagus, a biopsy is taken11–13 and stained with the immunohistochemical stains used in the diagnosis of cutaneous melanoma. The presence of melanosome (HMB45), melan-A and S100 protein are obligatory for the diagnosis of melanotic melanoma 14. If an oesophageal melanoma is detected an extensive examination must be performed for synchronous melanoma at cutaneous and ocular sites 15.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that melanoblasts originate and further differentiate into melanocytes in the oesophageal wall after migrating from the neural crest cells 1 2 4 8. The role of NRAS and BRAF mutations with the presence of KIT and PDGFRA gene has been demonstrated in the pathogenesis of PMME 11. Allen and Spitz12 constructed a diagnostic criteria for PMME; however, it was noted that only 40% of oesophageal melanomas fulfilled these criteria 2 4 13…”
Section: Discussionmentioning
confidence: 99%